Development of Articulate Storyline Media Assisted by Plickers Based on Problem Based Learning in History Subjects - Mandasari, Fabella Nada Kinanti; Soepeno, Bambang; Nirmala Putri, Rully Puji; Rieski Triyanto, Jefri; Prasetyo, Guruh; Budiman Nasution, Ahmad Arif (JURNAL HISTORICA, 2024)
This research aims to develop Articulate Storyline learning media assisted by Plickers based on Problem Based Learning in history subjects. The problems in this research are students who have difficulty focusing, are lazy, and have difficulty understanding what is explained by the teacher. Students also want to use PowerPoint, concept maps, illustrative images to make it easier to understand historical material. The research subjects in this study were class X IPS students at SMA Negeri 1 Glagah, Banyuwangi. This research is a type of Research and Development (R&D) research with the ASSURE development model as the development procedure in this research. The development of this media went through a validation testing stage consisting of validation by material, language and media experts, as well as user testing by educators and students. The results obtained were that material experts scored an average score of 4.6 in the outstanding category, media experts got an average score of 4.9 in the outstanding category and media experts got an average score of 4.9 in the outstanding category. For the educator user test, an average score of 4.59 was obtained. The results of the student user test were carried out twice, in the small group user test the average value was 4.7, and for the large group user test the average value was 4.6. Thus, research on Articulate Storyline learning media assisted by Plickers based on Problem Based Learning in history subjects has very good validity and can be used as a learning media.